Bibliometric Analysis: Research on the Utilization of Herbal Plant Extracts for Wound Treatment - Prasetyo, Sigit Nian; Soesanto, Edy; Redjeki, Sri; Pranata, Satriya (Babali Nursing Research, 2024)
Background: Herbs have been widely used in treating and managing various types of wounds. This study aims to analyze the research scope of utilizing herbal plant extracts for wound treatment. Methods: The method used in this study is to search for articles using the Dimensions application published from 2015-2023. Research is limited by selecting categories: Biomedical and clinical sciences, Biological sciences, Agricultural, Veterinary and Food sciences, and Pharmacology and Pharmaceutical sciences. The keywords used are "Herbs AND plant AND extracts AND wound healing." The search results in articles are then extracted using VOS-Viewer. The study used a minimum number of linkages of 10 terms. VOS-Viewer analysis shows that there are 4 clusters (red, green, blue, and yellow) that show the relationship between one topic and another. Results: Four keywords dominate each cluster: “medicinal plant,” “group,” “therapy,” and “cell.” Conclusions: VOS-viewer obtained information on the number of articles published about the use of herbal plant extracts for wound treatment, the number of publications each year, the most active authors in journal publications, and mapping from networks, overlays, and visuality density related to the novelty of research on the use of herbal plant extracts for wound treatment.